Maximum power point tracking control for wind turbines with battery storage system - Ismail Sh. B. Hburi; Hasan Fahad Al Kazaali; Ogoz BAYAT; Nibras Hazim Abbas Sarray Atab (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
In wind energy conversation systems (WECS), power quality and energy conversion efficiency are crucial aims of control algorithms. These two points are self-contradictory and difficult to trade off where enhancing the efficiency of conversion may also enhance instability of output signal as well. In current work, we submit a wind turbines control scheme to ensure regular power and achieve variable load requests in battery based variable speed PMGS system. In the submitted scheme, model predictive control (MPC) is joint with fuzzy logic to achieve the advantages of these two diverse approaches. The suggested controller could enhance the power reliability performance of the wind turbine. According to obtained results, the proposed topology overcomes the traditional proportional/integral (PI) model by achieving profits in the context of step-overshoot response and the measure of total harmonic-distortion of nearly 1.1 percent and 1.13 percent, respectively.